Market assessment on the incentives and disincentives for the adoption of sustainable practices along the tuna value chain in Region 12, Philippines. (December 2017) - Digal, Larry N.; Placencia, Shemaiah Gail P.; Balgos, Carol Q.
Abstract: With the world's increasing demand for tuna and the subsequent exhaustion of tuna stocks, this paper tries to assess the different attempts and/or practices that lead towards sustainability along the tuna value chain in the Philippines. In terms of economic gains, the net margins analysis, was used to measure the level of income of the actors which was considered as a factor that could possibly incentivize the adoption of sustainable practices, along with other market phenomena which were reviewed in this paper. These significant practices in the market include the provision of price premiums for the capture of mature tuna and the stringency of the market in terms of eco-labelling and certifications in contrast to the indifference of the local Philippine market in terms of preference. Lastly, having purse seine as a less sustainable method of tuna fishing, it was seen that there is a lack of incentive for them to adopt more sustainable practices.